2024
DOI: 10.1163/23524588-20240133
|View full text |Cite
|
Sign up to set email alerts
|

Alphitobius diaperinus larvae (lesser mealworm) as human food – An approval of the European Commission – A critical review

S.A. Siddiqui,
Y.S. Wu,
K. Vijeepallam
et al.

Abstract: Due to the increasing threat of climate change and the need for sustainable food sources, human consumption of edible insects or entomophagy has gained considerable attention globally. The larvae of Alphitobius diaperinus Panzer (Coleoptera: Tenebrionidae), also known as the lesser mealworm, have been identified as a promising candidate for mass-rearing as a food source based the on evaluation on several aspects such as the production process, the microbiological and chemical composition, and the potential all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 137 publications
0
2
0
Order By: Relevance
“…These minerals are crucial for various physiological functions, making this insect a nutritionally dense food source. The high iron content, in particular, is beneficial for addressing iron deficiency, while the presence of other minerals supports overall metabolic health [ 36 , 42 , 43 , 44 ]. Moreover, A. diaperinus exhibits an accelerated developmental cycle and enhanced reproductive capacity, leading to decreased production costs per unit mass.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These minerals are crucial for various physiological functions, making this insect a nutritionally dense food source. The high iron content, in particular, is beneficial for addressing iron deficiency, while the presence of other minerals supports overall metabolic health [ 36 , 42 , 43 , 44 ]. Moreover, A. diaperinus exhibits an accelerated developmental cycle and enhanced reproductive capacity, leading to decreased production costs per unit mass.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that people sensitive to house dust mites and crustaceans may experience cross-reactivity with these insect allergens. Additionally, it has been found that individuals allergic to prawns are at a higher risk of developing food allergies to mealworms and other insects [ 37 , 43 ]. Studies have shown that the microbiome associated with A. diaperinus can vary significantly depending on environmental conditions and storage methods [ 46 ].…”
Section: Introductionmentioning
confidence: 99%